(untitled) (Research, Society and Development, 2021)
To evaluate the influence of reciprocating single-file instrumentation with different working lengths (WL) on the reduction of planktonic bacteria and bacterial biofilm in Enterococcus faecalis-contaminated oval root canals. Methodology: Fifty-five human single-rooted canines were used. Fifty were inoculated with E. faecalis for 21 days for biofilm formation. To confirm the formation of biofilm adhered to the root canal wall, 5 contaminated samples from positive control group were analyzed by SEM. Samples were assigned into 3 groups (n = 15) according to working length determined, G+1 root canal preparation 1 mm beyond the apical foramen, G0 root canal preparation at the major foramen, and G-1 root canal preparation 1 mm short of the major foramen. Five roots were not inoculated to serve as a negative control. Bacteriological samples were collected prior to preparation, initial collection (S1), and after reciprocating instrumentation (S2) by disaggregating biofilm to quantify the reduction of planktonic bacteria and intracanal biofilm at different WL. Bacterial quantitation was performed using colony-forming units per milliliter (CFU / mL) count. Statistical analysis was performed at the significance level of 0.05. Results: No bacterial growth was observed in the negative control. All positive controls demonstrated bacterial growth; S1 from all teeth were positive for bacteria with no significant difference. The post-hoc analysis showed G+1 promoting a significantly higher disinfection than G-1 (p<0,05) and G-1 similar disinfection to G0 (P=962). Conclusion: Instrumentation as close as possible to major foramen or beyond it improves decontamination in oval root canals with reciprocating instrumentation.